Fluid-structure interaction of a foiling craft - Giovannetti, L. M.; Farousi, A.; Ebbesson, F.; Thollot, A.; Shiri, A.; Eslamdoost, A. (Journal of Marine Science and Engineering, 2022)
Hydrofoils are a current hot topic in the marine industry both in high performance sailing and in new passenger transport systems in conjunction with electric propulsion. In the sailing community, the largest impact is seen from the America`s cup, where boats are sailed at more than 50 knots (over 100 km/h) with 100% "flying" time. Hydrofoils are also becoming popular in the Olympics, as in the 2024 Olympic games 5 gold medals will be decided on foiling boats/boards. The reason for the increasing popularity of hydrofoils and foiling boats is the recent advances in composite materials, especially in their strength to stiffness ratio. In general, hydrofoils have a very small wetted surface area compared to the wetted surface area of the hull. Therefore, after "take-off" speed, the wetted surface area of the hull, and consequently the resistance of the boat, is reduced considerably. The larger the weight of the boat and crew and the higher the speeds, the greater the loads on the hydrofoils will be. The current research investigates the interaction effects between the fluid and structure of the ZP00682 NACRA 17 Z-foil. The study is carried out both experimentally, in SSPA`s cavitation tunnel, and numerically using a fully coupled viscous solver with a structural analysis tool. The experimental methodology has been used to validate the numerical tools, which in turn are used to reverse engineer the material properties and the internal stiffness of the NACRA 17 foil. The experimental flow speed has been chosen to represent realistic foiling speeds found in the NACRA 17 class, namely 5, 7, and 9 m/s. The forces and the deflection of the Z-foil are investigated, showing a maximum deflection corresponding to 24% of the immersed span. Finally, the effects of leeway and rake angles on the bending properties of the Z-foil are investigated to assess the influence of different angles in sailing strategies, showing that a differential rake set-up might be preferred in search for minimum drag.